Increasing Student Awareness of the Importance of Education Through Educational Seminars at SMKN 15 Pandeglang - Millah, I'anatul; Fakhitah; Pitrotussaadah; Farhan Ridzky; Muhamad Khaerul Insani; Shohibul Umam (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2024)
Education is an important component in improving human resources for sustainable development. Pasirpeuteuy Village, Cadasari District, Pandeglang Regency, has a very low level of education, with an average of only graduating from junior high school/high school. This obstacle is caused by economic problems and the lack of interest of students to continue their education to college level, some even do not continue their education because they want to get married. Against the backdrop of this situation, it is very important to encourage students to continue their studies through seminar activities. The purpose of this activity is to improve the quality of education of the Pasirpeuteuy Village community. This activity was carried out by KKN 10 UIN Sultan Maulana Hasanuddin Banten on August 7, 2024 at SMKN 15 Pandeglang, targeting 66 students of SMKN 15 Pandeglang. The method used was interactive material presentation with counseling between resource persons and students. The results of this activity had a positive impact by motivating them and inspiring the thinking of SMKN 15 Pandeglang students to continue their education.